Develop Total Productive Maintenance Checklists using Functional Based Approach - 'Adil, Nur Muhammad Malikul; Rian Dwi Aji Saputro (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
Total Productive Maintenance (TPM) is the most popular maintenance method in manufacturing industry. There are 8 TPM pillars, two of them are performing autonomous maintenance (AM) and preventive maintenance (PM) with specific guidance, which is called TPM Checklists. For well-established technology, the checklists are provided by machine vendor, and the users only need to follow them. However, for customized technology, users need to create the checklists by themselves. This situation requires specific guidance how to develop it. This research studies how to develop TPM checklist using functional based approach. Research was conducted by making TPM checklists for disc milling machine, then the developed checklists were validated to the existing TPM checklist built by the previous researchers. Results showed that the accuracy level reached 91.67%. It means that functional based approach can be an alternative solution to create and develop TPM checklists